1999
DOI: 10.1111/j.1540-8159.1999.tb06815.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Voltage Direct Current Delivered Through Unipolar Transvenous Leads: An Alternate Method for the Induction of Ventricnlar Fibrillation

Abstract: The induction of VF during testing of an ICD may not always be possible using either burst pacing or high energy T wave shocks. The purpose of this study was to evaluate the effectiveness of low energy DC stimulation for inducing VF in a porcine model. The VFT was measured using constant voltage stimuli and a step-up method in ten anesthetized pigs (25-30 kg). Stimuli of different durations (0.5, 1.0, 2.0 s) were delivered (unsynchronized) between a right ventricular apical coil and a subcutaneous test can. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The lack of VF induction in our simulations and experiments likely explains the lack of evidence in the literature for the use of a 9-V battery for such purposes in the rabbit, as opposed to its widespread use in species such as the pig (8,9,17,22) and dog (11,24), which are known to be easier in which to induce more complex arrhythmias (25) due to their relatively larger effective electrical size (19). Therefore, the larger effective size of other species may prevent the rapid self-termination of initial reentrant cycles induced by the battery, which may then likely degenerate into more complex, self-sustained fibrillatory-like activity.…”
Section: Relation To Other Speciesmentioning
confidence: 64%
See 1 more Smart Citation
“…The lack of VF induction in our simulations and experiments likely explains the lack of evidence in the literature for the use of a 9-V battery for such purposes in the rabbit, as opposed to its widespread use in species such as the pig (8,9,17,22) and dog (11,24), which are known to be easier in which to induce more complex arrhythmias (25) due to their relatively larger effective electrical size (19). Therefore, the larger effective size of other species may prevent the rapid self-termination of initial reentrant cycles induced by the battery, which may then likely degenerate into more complex, self-sustained fibrillatory-like activity.…”
Section: Relation To Other Speciesmentioning
confidence: 64%
“…All reports in the literature describing successful induction of VF via this method are almost exclusively in porcine (8,9,17,22) and canine (11,24) hearts, with some reports of its use in sheep (15) and guinea pigs (10), in addition to ex vivo human hearts (16). Intriguingly, though, there appear to be no reports of VF induction with a 9-V battery in the rabbit heart, potentially due to the noted difficulty in achieving self-sustained VF in healthy rabbit ventricles (3,12,14).…”
mentioning
confidence: 99%
“…Experiments lasted no longer than 4 h. Within 15 s after VF induction by epicardial, low energy DC stimulation (Euler et al, 1999;Viana et al, 2014), either unidirectional or multidirectional defibrillation was attempted. If the arrhythmia could be reversed, a shock of the same modality, but lower energy, was applied 5-15 min later.…”
Section: In Vivo Test Of the Defibrillatormentioning
confidence: 99%
“…5 In addition, application of AC or rapid ventricular stimulation for the induction of VF often results in a rapid nonclinical VT. 5,6 A prior animal study has shown that VF can be reliably induced with low voltage direct current (DC) stimulation using a single transvenous right ventricular (RV) electrode/defibrillator can system. 7 Studies suggested that DC induction could be an alternative tool to programmed stimulation or T shock to induce VF in ICD patients. 6,7 To assess the utility of DC as a method of VF induction, the authors carried out a randomized clinical trial in patients undergoing ICD implantation.…”
Section: Introductionmentioning
confidence: 99%